تطبيق نموذج التعلم الاكتشافي لتحسين إتقان المفردات لدى الطلاب لمستوى المتوسطة في بانيونجي - Khozin , Nur; Insaniyah, Anyes Lathifatul (Yayasan Mutiara Hati Moeslem, 2025)
The Discovery Learning Model is a learning process where students are able to assimilate a concept by observing, digesting, understanding, categorizing, hypothesizing, explaining, and drawing conclusions. The purpose of this research is to determine the application of the discovery learning model in vocabulary learning for MTs-level students. The research method used is descriptive qualitative research. The results of this study indicate that the discovery learning model in vocabulary teaching applied by the teacher in the classroom begins with the teacher playing an audio recording of the vocabulary to be taught, and the students listen until the audio is finished. Then, the teacher pronounces the vocabulary while showing pictures, and the students imitate the teacher and look at the displayed pictures. Next, the students search for relevant information to determine the vocabulary by opening the LKS book chapter on vocabulary to recall the vocabulary that the teacher has played. After that, the students discuss with their group members to determine the vocabulary that has been played and write it down to memorize it. Finally, the students present the vocabulary notes they have compiled with their group members.